Echinococcosis of spleen causing the displacement of left kidney: A case report (Indian Journal of Case Reports, 2020)
Hydatid disease is a parasitic infection caused by the Echinococcus genus. Giant isolated splenic hydatid cyst is very rare in occurrence. In this case report, we present a 50-year-old female with a giant splenic hydatid cyst displacing the ipsilateral kidney and aorta from its normal position. The clinical, imaging and laparotomy findings are discussed.